IMMUNOHISTOCHEMICAL DETECTION OF NEUROFILAMENTS IN THE SCIATIC NERVE, WHICH REGENERATES AFTER NEUROTOMY AND SURGICAL SUTURING - Yashchyshyn, Z.M.; Ziablitsev, S.V.; Zaiats, L.M. (World of Medicine and Biology, 2022)
The purpose of the study was to determine the expression of neurofilaments in the sciatic nerve, which regenerates after neurotomy and surgical suturing, and to compare the effect of laser irradiation of different spectrum. The experiment was performed on 20 laboratory Wistar rats (200–250 g) with crossing the left sciatic nerve and suturing with an epineural suture end to end 30 minutes after neurotomy. 90 days later, an immunohistochemical study was performed using monoclonal anti-neurofilament antibodies (clone 2F11; Thermo Fisher Scientific; USA). In the control group (without the use of a laser), the main type of regenerated nerve fiber was a small diameter myelinated fiber (2–3 μm), the number and density of the myelin sheath of axons were low, and the growth of connective tissue was high. Neurofilaments expression is weak (up to 25 % of neurons) or absent. The use of laser irradiation of the green spectrum (560 and 520 nm) allowed to significantly increase the level of neurofilaments expression, and the use of irradiation of the blue spectrum (450–480 nm) – to restore the structure of the sciatic nerve.
Keywords: nerve regeneration; neurofilaments; expression; immunohistochemistry